Quills [videorecording (DVD)] - Kaufman, Philip, 1936-; Rush, Geoffrey, 1951-; Winslet, Kate; Phoenix, Joaquin; Caine, Michael; Wright, Doug, 1962- (Twentieth Century Fox Home Entertainment, 2001)
History's most infamous sexual adventurer lives in a madhouse, where a beautiful laundry maid helps him smuggle his erotic stories to the printer, defying orders from the asylum's priest.